Pendidikan Kristiani bagi komunitas iman di tengah krisis kepercayaan antaranggota - Merri Natalia Situmorang (KURIOS, 2023)
The crisis of trust among members of faith communities is an increasingly worrying phenomenon in the context of contemporary churches, including in Indonesia. When interpersonal relationships within faith communities are eroded by mistrust, betrayal, and unresolved internal conflicts, the church's ecclesial and missional functions are fundamentally disrupted. This article examines the strategic role of Christian Education (CR) in responding to the crisis of trust within faith communities. Using a theological-qualitative research method grounded in literature review, this article investigates the theological foundations, sociological framework, and pedagogical implications of this issue. The main argument of this article is that transformative CR, which is based on the habitus of faith, faithful presence, and the koinonia paradigm, has the formative capacity to restore and rebuild trust among members of the faith community in an authentic way. The findings of this article affirm that the restoration of trust is not merely a social project but a theological response to God's call for a community that lives in truth, love, and fellowship, transcending the calculation of personal interests.   Abstrak Krisis kepercayaan antaranggota dalam komunitas iman merupakan fenomena yang kian mengkhawatirkan dalam konteks gereja kontemporer, termasuk di Indonesia. Ketika relasi interpersonal di dalam komunitas iman terkikis oleh ketidakpercayaan, pengkhianatan, dan konflik internal yang tidak terselesaikan, fungsi eklesial dan misional gereja menjadi terganggu secara fundamental. Artikel ini bertujuan mengkaji peran strategis Pendidikan Kristiani (PK) dalam merespons krisis kepercayaan antaranggota komunitas iman. Menggunakan metode penelitian teologis-kualitatif berbasis studi pustaka, artikel ini menyelidiki landasan teologis, kerangka sosiologis, dan implikasi pedagogis dari persoalan tersebut. Argumen pokok artikel ini adalah bahwa PK yang transformatif, yang bertumpu pada habitus iman, kehadiran setia, dan paradigma koinonia, memiliki kapasitas formatif untuk memulihkan dan membangun kembali kepercayaan antaranggota komunitas iman secara autentik. Temuan artikel ini menegaskan bahwa pemulihan kepercayaan bukan sekadar proyek sosial, melainkan respons teologis terhadap panggilan Allah bagi komunitas yang hidup dalam kebenaran, kasih, dan persekutuan yang melampaui kalkulasi kepentingan pribadi.